2015
DOI: 10.1542/neo.16-2-e94
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Clinical Research Design, Part 2: Principles

Abstract: This is the third article covering core knowledge in scholarly activities for neonatal physicians. In this article, we discuss various principles of epidemiology and clinical research design. A basic knowledge of these principles is necessary for conducting clinical research and for proper interpretation of studies. This article reviews bias and confounding, causation, incidence and prevalence, decision analysis, cost-effectiveness, sensitivity analysis, and measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…However, the results were less convincing for the symptom subscales CD and GAD. The low prevalence of CD and GAD could partly explain this as it is challenging to reliably screen for disorders of low prevalence (24). In line with earlier studies (12,13), ADHD could be reliably identified with both the BCFPI and the CBCL.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, the results were less convincing for the symptom subscales CD and GAD. The low prevalence of CD and GAD could partly explain this as it is challenging to reliably screen for disorders of low prevalence (24). In line with earlier studies (12,13), ADHD could be reliably identified with both the BCFPI and the CBCL.…”
Section: Discussionsupporting
confidence: 70%
“…However, the results were less convincing for the symptom subscales CD and GAD. The low prevalence of CD and GAD could partly explain this as it is challenging to reliably screen for disorders of low prevalence ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence from available prospective cohort studies and RCTs has both strengths and also weaknesses (106). Most prospective cohort studies have investigated risk factors in large populations with long follow-up periods, but one can never exclude residual confounding in cohort studies.…”
Section: Current Status Of Research In Relation To Prevention Prediamentioning
confidence: 99%